Fast Photoswitching Azo Dyes - Hegde, Gurumurthy; Yuvaraj, A. R.; Wan, Sinn Yam; M. M., Yusoff (John Wiley & Sons, 2015)
Fast photoswitching azobenzene molecules were incorporated into isoflavone moieties. These molecules exhibit a liquid crystalline nematic state at certain temperature intervals. UV/Vis spectrophotometry investigations on solutions reveal that E/Z conversion takes place around 1 s, whereas thermal back relaxation, namely Z/E, takes around 6 min. This is the first example of fast photoswitching isoflavones in solution. This study has potential to create optical data storage devices when transferred to solid surfaces.